EXPLORING THE CONCEPT OF HEROISM IN J.R.R. TOLKIEN’S THE LORD OF THE RINGS - Xayrulloyeva Nigorabegim Ne'matullo qizi (Prospects for innovative technologies in science and education, 2025)
This article explores the multifaceted concept of heroism in J.R.R. Tolkien’s The Lord of the Rings. It highlights how Tolkien redefines heroism through characters such as Frodo, Sam, Aragorn, Éowyn, and Faramir — focusing not only on strength and battle but on moral courage, humility, loyalty, and self-sacrifice. The article emphasizes that both great warriors and ordinary individuals can embody heroism, and that collective efforts, moral choices, and resilience are central to Tolkien’s portrayal of true heroism.